Effect of bulk modulus on performance of a hydrostatic transmission control system - Akkaya, Ali Volkan (SPRINGER INDIA, 2006)
In this paper, we examine the performance of PID (proportional integral derivative) and fuzzy controllers on the angular velocity of a hydrostatic transmission system by means of Matlab-Simulink. A very novel aspect is that it includes the analysis of the effect of bulk modulus on system control. Simulation results demonstrates that bulk modulus should be considered as a variable parameter to obtain a more realistic model. Additionally, a PID controller is insufficient in presence of variable bulk modulus, whereas a fuzzy controller provides robust angular velocity control.
Keywords: hydrostatic transmission; bulk modulus; PID (proportional integral derivative); fuzzy controller; Engineering